2007
DOI: 10.1542/peds.2006-0893
|View full text |Cite
|
Sign up to set email alerts
|

Early-Life Risk Factors for Occurrence of Atopic Dermatitis During the First Year

Abstract: The association of atopic dermatitis in infancy with reduced neonatal macrophage inflammatory protein-1beta levels suggests a link with immature immune responses at birth. Stratum corneum barrier disruption in atopic dermatitis may involve impairment of cutaneous adaptation to extrauterine life. The majority of risk factors had different effects on infant eczema and atopic dermatitis, indicating different causes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 30 publications
5
33
0
2
Order By: Relevance
“…72,73 The development of atopic disease is the result of complex interactions between genetic and environmental factors, 74 with several studies showing that the risk of developing atopic dermatitis is strongly associated with a family history of the condition. A recent prospective birth cohort study of 213 infants in Japan found that maternal atopic dermatitis was a risk factor for development of atopic dermatitis in the first year of life, 75 with similar findings reported in studies in Denmark 76 and Taiwan. 72 Paternal history of atopic dermatitis also appears to be a risk factor, although it is less strongly predictive of developing atopic dermatitis in the first 6 months of life than maternal history.…”
Section: Infants At High Risk Of Atopic Dermatitissupporting
confidence: 71%
“…72,73 The development of atopic disease is the result of complex interactions between genetic and environmental factors, 74 with several studies showing that the risk of developing atopic dermatitis is strongly associated with a family history of the condition. A recent prospective birth cohort study of 213 infants in Japan found that maternal atopic dermatitis was a risk factor for development of atopic dermatitis in the first year of life, 75 with similar findings reported in studies in Denmark 76 and Taiwan. 72 Paternal history of atopic dermatitis also appears to be a risk factor, although it is less strongly predictive of developing atopic dermatitis in the first 6 months of life than maternal history.…”
Section: Infants At High Risk Of Atopic Dermatitissupporting
confidence: 71%
“…20,21 Based on results from these studies, a parental history of allergic disease would be the most important factor for the development of eczema, but some other studies showed an association only with a maternal history of allergic disease and not with a paternal history. 22,23 The variability of the results may be due to the difference in the ethnicity of the enrolled populations, differences in eczema phenotype, or other factors. Ethnicity and a parental history of allergic disease indicate a genetic influence on the development of eczema; however, differences in genetic admixture do not support a major role for genetics in explaining the ethnic differences on the development of eczema.…”
Section: Discussionmentioning
confidence: 99%
“…6,22,24,25 The influence of environmental exposure that occurred during critical developmental periods of the immune systems may increase the likelihood of allergic disease. Prenatal exposures may influence the programming and development of neonatal immune response.…”
Section: Discussionmentioning
confidence: 99%
“…With this assay, the cytokines were quantitated, including IL-1β, IL-2, IL-4, IL-5, IL-7, IL-10, IL-12, IL-13, and IL-17, IFN-γ, TNF-α, granulocyte/ macrophage colony-stimulating factor, granulocyte colony-stimulating factor, monocyte chemotactic protein (MCP)-1, and macrophage inflammatory protein (MIP)-1β [25]. Most standard curves ranged between 0.2 pg/ml and 3,200 pg/ml.…”
Section: Multiplex Cytokine Array Analysismentioning
confidence: 99%